Informing and transforming language teacher education pedagogy - Johnson, Karen E.; Golombek, Paula R. (Language teaching research : LTR, 2020)
Given emerging trends in where, why, how, and to what end English language teachers are being prepared, we argue that greater attention to the design, enactment, and consequences of language teacher education (LTE) pedagogy is critical in order to meet the needs of current and future English language teachers in an increasingly diverse, mobile, unequal, and globalized world. Through our experiences and conviction as researchers and teacher educators, we position a Vygotskian sociocultural theoretical perspective as foundational to informing and transforming LTE pedagogy. In this essay, we offer eight interrelated propositions that we believe constitute LTE pedagogy as a central domain for the knowledge-base of LTE.